RADIATION MEASUREMENT OF RADIOISOTOPE IN MINERAL DEPOSIT AT SUBDISTRICT OF MIDDLE KUPANG WEST TIMOR ISLAND INDONESIA - Bartholomeus Pasangka; Frederika Rambu Ngana (Jurnal Fisika : Fisika Sains dan Aplikasinya, 2020)
The general objective of this work was investigation of radioisotope distribution and accumulation center in mineral deposit at sub-district of Middle Kupang West Timor Island Indonesia. The purposes of research were: to map of radioisotope distribution in the mineral deposit, to estimate area of radioisotope accumulation center in the mineral deposit, to establish range of nuclear radiation counts in the center region of radioisotope content in mineral deposit. The general methods used in this research were observation, survey, mapping, analysis, and interpretation. Procedures detail of research consists of: observe and identify the potential region and plot gridding, calibrate equipment necessary, measure background count in around of survey location and nuclear radiation in the survey location, plot of three dimensions curve and contour after corrected by background count. Based on geology information or geology data (drilling data) three depth levels determined (about 20 m, 40 m and 60 m), Radiation powers were calculated for estimation of accumulation center of radioisotope in deposit mineral, and contour and three dimensions curves of radiation power of radioisotope in deposit mineral were plotted. Results: Based on three dimensional curves and contour map (radiation counts and radiation powers on three levels) of radioisotope in mineral deposit respectively was distributed on area 3.00 x 106 m2, and 1.56 x 104 m2. The interval of radiation counts of radioisotope in mineral deposit was 10 counts per minute-137 counts per minute. Keywords: Radiation, measurement, radioisotope, mineral, deposit